Meta-paradigmatic cognitive perspective in management studies. Argumenta Oeconomica, 2012, Nr 2 (29), s. 33-51 - Sułkowski, Łukasz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
The paper proposes the use of the meta-paradigmatic analysis in investigating organizational problems. First, I analyse the phenomenon of multi-paradigmaticism in management studies. I will characterize four management paradigms accentuating the differences between them. Then, I will point to the potential relationships between the paradigms stressing the possibilities of combining cognitive perspectives. The meta- paradigmatic perspective can be particularly useful in the following fields: the theory of organization, organizational culture, knowledge management, human capital management and the methodology of management
Argumenta Oeconomica, 2012, Nr 2 (29), s. 33-52
Keywords: management paradigms; meta-paradigmatic method; paradigms of social sciences; paradygmaty zarządzania; teoria organizacji; zarządzanie wiedzą; kultura organizacyjna